Development of the Hearing Dog Evaluation and Reporting Overview (HERO): A Novel Measure for Hearing Dog Welfare - Charis Koh; Holly Chillingworth; Carlie Driscoll; Jessica Hill; Edward Narayan (Animals)
This paper delves into the development and implications of the Hearing Dog Evaluation and Reporting Overview (HERO) tool, which is a novel initiative built on the Five Domains animal welfare model to comprehensively assess the wellbeing of Hearing Dogs. The HERO’s creation involved two phases. In Phase One, an expert panel was surveyed using an electronic Delphi technique to gather consensus on items for the tool. This phase culminated in 28 items, exhaustively covered the Five Domains, and offered a holistic evaluation of Hearing Dog welfare. Phase One complemented existing assistance animal standards and emphasised the importance of a quality environment and continuous wellbeing monitoring. Phase Two involved 23 Hearing Dog owners, to assess the tool’s usability, particularly its user-friendliness and perceived value. Concerns about handlers’ ability to identify welfare indicators were raised, highlighting the need for additional development of resources and guidance. This preliminary study has shown that the HERO is a promising tool for understanding and promoting Hearing Dog welfare. Future research will look to validate the tool by drawing from expert observations and physiological measures, tailoring survey questions, and creating a user-sharing platform.